HUBUNGAN INDEKS MASSA TUBUH DENGAN KADAR KOLESTEROL PADA KARYAWAN DAN MAHASISWI POLITEKNIK KUDUS - Yoga Adhi Dana; Hanifah Maharani (ARKA INSTITUTE, 2022)
Non-communicable diseases cause 71% of deaths in the world. Dyslipidemia has been established as the cause of various non-communicable diseases such as obesity (PERKENI, 2019). A person's weight gain is in line with the increase in serum cholesterol. This study aims to find out the correlation of body mass index with cholesterol levels in employees and students of Kudus Polytechnic. This study is a type of observational study using Posbindu secondary data including name, anthropometric (TB, BB), cholesterol level data, and disease history. So as to complete the basic data respondents researchers use additional questionnaires to dig up the data. The sample were students and employees of Kudus Polytechnic with purposive sampling techniques. Data analysis uses pearson correlation test and relationship strength (r). Pearson test results show values (p<0.05) so that BMI variables have a meaningful relationship to blood cholesterol levels. Correlation (r = 0.4) indicates a moderate correlation. The higher a person's BMI, the higher his blood cholesterol levels. In external variables, cholesterol levels have a meaningful relationship with age. The strength of the relationship is moderate and the positive direction so that the more mature the age then there is an increase in cholesterol levels.